Analisis Kemampuan Pemecahan Masalah Higher Order Thinking Skill (HOTS) Siswa Berdasarkan Gaya Kognitif Field-independent dan Field-dependent - Satila, Susena; Prayitno, Sudi; Novitasari, Dwi; Baidowi, Baidowi (FKIP Universitas Mataram, 2024)
This study aims to describe the HOTS problem silving ability of studentsin solving quadratic eguation problem based on field-independent and field-dependent cognitive styles. The type of research used is descriptive qualitative research. The subjects in this study were 6 grade 9th students in one of the State MTs in Mataram city consisting of 3 field-independent students and 3 field-dependent students seleceted by purposive sampling technique. Data collection was conducted using the GEFT test instrument, HOTS problem solving test questions, and interview guidelines. The data analysis technique used the Miles and Huberman stages, which include data reduction, data presentation, and conclusion drawing. The results of the study showed that: (1) Students with field-independent cognitive style had a very good level of problem solving ability in the stages of understanding the problem, executing the plan, and checking back, and a good category in the planning stage; (2) Students with field-dependent cognitive style had a very good level of HOTS problem solving ability in the stage of understanding the problem, a low category in the planning stage and executing the plan, and a very low category in the checking back stage.